Etymology in Plato’s Sophist - Sedley, David (Hyperboreus, 2019)
The etymological method displayed at considerable length in the Cratylus is widely assumed to be intended by Plato as an object of ridicule. In my 2003 monograph Plato’s Cratylus I resisted this assumption. In the present paper I seek to strengthen my case by arguing that in Plato’s major work on philosophical logic, the Sophist, the same method is re-employed twice, at 221 a–c and 228 b–e, for entirely serious purposes.